Hydrothermal treatment: An efficient food waste disposal technology - Zhang, Xinyan; Qin, Qingyu; Sun, Xun; Wang, Wenlong (Frontiers in Nutrition, 2022)
The quantities of food waste (FW) are increasing yearly. Proper disposal of FW is essential for reusing value-added products, environmental protection, and human health. Based on the typical characteristics of high moisture content and high organic content of FW, hydrothermal treatment (HTT), as a novel thermochemical treatment technology, plays unique effects in the disposal and utilization of FW. The HTT of FW has attracted more and more attention in recent years, however, there are few conclusive reviews about the progress of the HTT of FW. HTT is an excellent approach to converting energy-rich materials into energy-dense fuels and valuable chemicals. This process can handle biomass with relatively high moisture content and allows efficient heat integration. This mini-review presents the current knowledge of recent advances in HTT of FW. The effects of HTT temperature and duration on organic nutritional compositions (including carbohydrates, starch, lipids, protein, cellulose, hemicellulose, lignin, etc.) and physicochemical properties (including pH, elemental composition, functional groups, fuel properties, etc.) and structural properties of FW are evaluated. The compositions of FW can degrade during HTT so that the physical and chemical properties of FW can be changed. The application and economic analyses of HTT in FW are summarized. Finally, the analyses of challenges and future perspectives on HTT of FW have shown that industrial reactors should be built effectively, and techno-economic analysis, overall energy balance, and life cycle assessment of the HTT process are necessary. The mini-review offers new approaches and perspectives for the efficient reuse of food waste.